The Genealogy of Philosophy as the Foundation of Science: a Literature Study on History, Terminology, and Classification - Ahmad Atif Maulana; Bahij Hisyam Abiyyu (Global Journal of Islamic Education, 2025)
This study investigates the historical and conceptual interconnections between philosophy and science as epistemological foundations. Employing a literature-based approach, it traces how philosophy has not only served as the origin of scientific disciplines but also continues to provide a reflective, critical, and normative framework for their development. The findings suggest that science has never been entirely autonomous; it consistently relies on philosophical assumptions concerning reality, logic, and truth. Comparative insights from Western and Eastern traditions enrich the epistemological discourse, combining rational analysis with holistic perspectives. Case studies on the role of philosophy in research ethics such as the Nuremberg Code, Hans Jonas’s ethical reflections, and social hermeneutics highlight its enduring relevance in safeguarding science as a humane and responsible endeavor. The study concludes that a comprehensive understanding of science is unattainable without engaging its philosophical genealogy, and that the integration of philosophy and science is indispensable for building knowledge that is value-conscious, reflective, and sustainable.